Pendeteksi Gerakan Pada Vidio Menggunakan Pyton dan OpenCV - Supiyandi Supiyandi; Andriani Sitorus; Nurul Fitriah; Havni Virul; Syawaliah Putri Rangkuti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Motion detection is an important process in computer vision to analyze activities in videos. This study implements a simple system to detect motion in video files using Python and the OpenCV library. The system works by comparing consecutive frames in a video to detect changes and mark areas that experience motion. The implementation shows satisfactory results on various sample videos. This study provides a solution that is easy to implement and can be used in applications such as video analysis and computer-based monitoring.